PEMILIHAN MAHASISWA BERPRESTASI MENGGUNAKAN ALGORITMA AHP (STUDI KASUS: FAKULTAS TEKNIK UBB) - Tou, Nurhaeka; Endraswari, Putri Mentari; Nur, Yohani Setiya Rafika (University of Muhammadiyah Tangerang, 2023)
The Selection of outstanding students at the Faculty of Engineering is an activity that is routinely carried out every year. It starts with each department selecting student candidates who are considered outstanding and collecting some data such as GPA, certificates of academic or non-academic achievements, and certificates of organizational history. Furthermore, representatives of each department follow the selection at the faculty level. In the process of selecting outstanding students, the faculty forms a team that will assess the outstanding student candidates. However, the process is still done manually and takes a long time to process the data. In addition, the manual processing of high-achieving student selection scores is prone to data processing errors which ultimately lead to inaccuracies in the assessment results. Therefore, based on this problem, a decision support system (DSS) is needed to assist the Faculty in determining one of the outstanding students using the AHP method. The criteria that become input in the selection of outstanding students are GPA, scientific papers, number of academic achievement certificates, non-academics, and English language skills. The results of this study indicate that the AHP method can determine alternative recommendations for outstanding students based on the specified input criteria with a consistency value of 0.56.